The golden age of Indian Buddhist philosophy - Westerhoff, Jan (Oxford history of philosophy, 2018)
Jan Westerhoff unfolds the story of one of the richest episodes in the history of Indian thought, the development of Buddhist philosophy during the first millennium CE. He aims to offer the reader a systematic grasp of key Buddhist concepts such as non-self, suffering, reincarnation, karma and nirvana